Digital Storytelling For Vocabulary Development In Elementary English Learning - Siregar, Tiarnita Maria Sarjani Br; Humaira, Najwa Utami; Ginting, Fitriani Meslin Br (English Education Journal, 2026)
This study investigates the role of digital storytelling in enhancing English vocabulary development among elementary school students. Vocabulary is a fundamental component of language proficiency; however, traditional teaching methods often result in low student engagement and limited retention. Therefore, this study aims to explore how digital storytelling can serve as an effective instructional strategy in vocabulary learning. The research employs a qualitative literature review method, analyzing relevant studies published between 2021 and 2026 using a systematic selection process based on PRISMA guidelines. The findings reveal that digital storytelling significantly improves students’ vocabulary size, contextual understanding, and retention through the integration of multimedia elements such as text, images, audio, and video. In addition, this approach increases students’ motivation, participation, and confidence in learning English. The study concludes that digital storytelling provides a meaningful, interactive, and student-centered learning experience that addresses the limitations of conventional methods. This research contributes to the field of English language teaching by offering a comprehensive synthesis of recent studies and highlighting digital storytelling as an innovative and effective strategy for vocabulary instruction at the elementary level.